2005
DOI: 10.1097/00019501-200506000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mesenchymal stem cell transplantation on extracellular matrix after myocardial infarction in rats

Abstract: Our results demonstrated that MSC transplantation could inhibit LV remodeling and improve heart function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 26 publications
2
32
0
3
Order By: Relevance
“…In the present study, we did not find any detectable MMP-1 mRNA expression, which is consistent with the investigation by Li et al [29]. Additionally, we did not find any difference at the protein production level of MMP-1 among the three experimental groups at week nine post-MI, which is accordance with our previous study [30]. We speculate that MMP-1 expression is probably augmented temporarily after MI and returns to normal level thereafter.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we did not find any detectable MMP-1 mRNA expression, which is consistent with the investigation by Li et al [29]. Additionally, we did not find any difference at the protein production level of MMP-1 among the three experimental groups at week nine post-MI, which is accordance with our previous study [30]. We speculate that MMP-1 expression is probably augmented temporarily after MI and returns to normal level thereafter.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, direct injection of human stem cells-in particular, mesenchymal stem cells-into ischemic rat myocardium decreased fibrosis, and that resulted in the prevention of systolic and diastolic LV dysfunction without evidence of myocardial regeneration (52). Additionally, stem cell transplantation significantly attenuated the increase in cardiac expression of collagen types I and III, and TGF-␀ in the infarcted myocardium (53). Because stem cells express a number of molecules involved in the biogenesis of extracellular matrix such as adrenomedullin, thymosin-␀, thymocollagenase, MMPs, serine proteases, and their inhibitors, it has been suggested that transplanted stem cells can inhibit fibrosis through paracrine actions (54).…”
Section: Alterations Of Collagen Matrixmentioning
confidence: 99%
“…Transplanted MSCs reduce myofibroblasts through releasing MMPs (Almalki and Agrawal, 2016;Mias et al, 2009). In MI rat models, implanted MSCs reduce the expression of collagen types I and III, tissue inhibitor of metalloproteinase-1 (TIMP-1), MMP2, MMP9, and transforming growth factor-beta (TGF-beta) (Nagaya et al, 2005;Xu et al, 2005). It is interesting that transplanted MSC cardiomyocyte (MSC-CM) also express the ability to reduce the scarring process by downregulating fibroblast proliferation and inhibiting the expression of collagen type I and type III in myofibroblasts (Ohnishi et al, 2007a;Ohnishi et al, 2007b).…”
Section: Impact On Extracellular Matrix (Ecm) and Reduction Of Scar Fmentioning
confidence: 99%